CULTURAL CONTENT IN ENGLISH TEXTBOOK FOR DEAF STUDENTS AT DISABLE SENIOR HIGH SCHOOL - Nor Fitriansyah; Masni Usman; Surono Surono (Universitas Islam Sumatera Utara (UISU), 2021)
This study explores the cultural content represented in the English Textbook used by the deaf students at disable senior high school or SMALB (Tuna Rungu). This book was published by Kemendikbud of Indonesia in 2016. This study was categorized as Descriptive qualitative research. The method used in this study is textbook content analysis. To collect the data, the writers selected the text, pictures and activities presented in each unit of the textbooks. Meanwhile, to analyze the data, the writers adapted two different frameworks. The first framework was used to explore what cultures are represented in the textbook (types of culture). The second framework was used to explore how the cultures were represented in the textbook (sense of culture). There are 157 cultural contents found in the Tunarungu Bahasa Inggris SMALB Grade XI 2016 book. By Type of Culture, the 157 cultural contents were divided into 60 Source Culture, 94 Target Culture and 3 International culture. Meanwhile, in terms of Sense of Culture, the 157 cultural contents were divided into 5 Aesthetic Senses, 3 Sociological Senses, 59 Semantic Senses and 90 Pragmatic Senses.